Penghitungan Unit Cost pada Ekokardiografi Jantung dengan Metode ABC Berdasarkan Tarif INA-CBG’s di RSAL Dr. Oetojo Sorong Papua Barat Daya - Rhegy Seno Pratama; Purwadhi Purwadhi; Rinawati Rinawati (Pusat riset dan Inovasi Nasional, 2025)
This study aims to calculate the unit Cost of echocardiography services at RSAL dr. Oetojo Sorong, West Papua, using the Activity-Based Costing (ABC) method and compare it with the applied INA-CBG’s tariff. The research method employed is a quantitative descriptive approach focusing on direct Cost analysis, overhead Costs, and Cost allocation based on activities. The data used includes primary data obtained from direct observation and interviews, as well as secondary data such as financial reports and hospital medical records. The results show that the unit Cost of echocardiography services calculated using the ABC method is higher than the INA-CBG’s tariff, indicating a disparity between the standard tariff and actual Costs. The application of the ABC method provides significant benefits to RSAL dr. Oetojo Sorong, such as identifying Cost-intensive activities, improving operational efficiency, and providing transparency in Cost management. This study also recommends that hospital management evaluate service tariffs and that BPJS Kesehatan review the alignment of INA-CBG’s tariffs with the actual Costs of healthcare services.